SERUM ELECTROLYTES IN CARDIOMYOPATHY PATIENTS AND ITS ASSOCIATION WITH MORBIDITY AND ADVANCE NYHA CLASSIFICATION - Abdul Qadir Bhutto1, Nandlal Rathi2, Jagdesh Kumar3, Abdul Aziz Sahito4, Kartik Kumar Rathi5, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2016)
OBJECTIVE: The aim behind this study was to scientifically assess the serum electrolytes in cardiomyopathy patients and its association with morbidity and advance NYHA classification. PATIENTS AND METHODS: A prospective cross-sectional study has been conducted in the department of cardiology Isra University Hospital Hyderabad through a convenience sampling technique. All the patients who were diagnosed cases of Cardiomyopathy (any type) and having age more than 16 years of both gender presented in advance NYHA (III – IV) classification were included in our study. Data were entered and analyzed by using Statistical Package for the Social Sciences version 19.0. RESULTS: The mean age of patients was 38.18 years (16.34 ± SD) and the study subjects consisted majority of males (59.01%). Out of 122 patients majority of the patients were presented between the age group of 41 – 55 years (N = 60, 49.18%). Most of the admitted patients presented in NYHA classification IV as compared to NYHA III, 59.83% (N = 73) and 40.16% (N = 49), respectively. Overall frequency of electrolytes deficiency in hospitalized patients was 47 (38.52%). CONCLUSION: Patients presented in NYHA classification III were more likely to have Hyponatremia and Hypobicarbonatemia while patients presented in NYHA classification IV were significantly has Hypernatremia, Hyperkalemia, and Hyperbicarbonatemia.